Optimized inversion‐time schedules for quantitative T1 measurements based on high‐resolution multi‐inversion EPI - Cohen, Ouri; Polimeni, Jonathan R. (Magnetic resonance in medicine, 2018)
Purpose Demonstrate an optimized multi‐inversion echo‐planar imaging technique to accelerate quantitative T1 mapping by judicious selection of inversion times for each slice. Methods Slice ordering is optimized to maximize discrimination between tissues with different T1 values. The optimized slice orderings are tested in the International Society for Magnetic Resonance in Medicine/National Institute of Standards and Technology phantom and compared with an unoptimized 21‐measurement acquisition. The utility of the method is demonstrated in a healthy subject in vivo at 3 T and validated with a gold‐standard inversion‐recovery sequence. The in vivo precision of our technique was tested by repeated scans of the same subject within a scan session and across scan sessions, occurring 28 days apart. Results Phantom measurements yielded good agreement (R2 = 0.99) between the T1 estimates from the proposed optimized protocol, reference values from the National Institute of Standards and Technology phantom and gold‐standard inversion‐recovery values, as well as a negligible estimation bias that was slightly lower than that from the unoptimized 21‐measurement protocol (0.74 versus 19 ms). The range of values for the scan–rescan coefficient of variation was 0.86 to 0.93 (within session) and 0.83 to 0.92 (across sessions) across all scan durations tested. Conclusions Optimized slice orderings allow faster quantitative T1 mapping. The optimized sequence yielded accurate and precise T1 maps. Magn Reson Med 79:2101–2112, 2018. © 2017 International Society for Magnetic Resonance in Medicine.